Benchmarking E-government: A Global Perspective - United Nations Department of Economic; Social Affairs (United Nations, 2022)
The study’s primary goal was to objectively present facts and conclusions that define a country’s e-government environment and demonstrate its capacity to sustain online development. This was accomplished by a comparative analysis of fundamental information and communication technology (ICT) indicators and critical human capital measures for each UN Member State. The final measure or E-government Index Could be useful tool for policy-planners as an annual benchmark.